Understanding young South African students' participation in local government - Tracey, Lauren Louise (My University, 2018)
The common narrative of social movements and protest action in recent years, indicates that young eole globally are doinating suh oveents n outh fria, students’ ontinued engageent in protests around politics and public issues at the local level, as well as their low levels of participation in formal democratic processes such as elections, calls for an assessment on whether students are knowledgeable and understand the role of local government, as well as local governance. This study looks at young outh frian students’ (1-24 years) knowledge and understanding of local government, and local governance in the Johannesburg Metropolitan. For the purpose of this qualitative research study, 56 young students in two universities and two TVET colleges in the Johannesburg metropolitan were interviewed through 35 semi-structured in-depth, one-on-one interviews, and three focus group discussions. This study confirms that students present a very narrow knowledge and understanding of democratic governance and the political system at the local level. This, it is argued, is a key reason behind their lack of engagement and participation at the local level, as well as their identification of protests as the only effective form of political activism. This study also indicates that, desite students’ awareness of traditional olitial latfors suh as eletions and taking art in community meetings, their perceptions of poor local leadership, eroding trust in traditional democratic institutions, patronage party politics and general disillusionment with the political future of the country, are hindering these students’ artiiation in loal governane
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Arts in Sociology, Johannesburg, February 2018
Keywords: College students--Political activity--South Africa; Higher education and state--South Africa; South Africa--Politics and government